Prediction of Motion Responses of Ship Shape Floating Structure using Diffraction Potential - Siow, C.L.; Koto, J.; Pauzi, M.; Yasukawa, H.; Matsuda, A.; Terada, D. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
This paper reviewed the capability of the proposed programming coded based on diffraction potential theory to predict a ship shape floating structure’s motion response. This paper briefly presents the procedure to apply the diffraction potential theory to simulate the ship shape floating structure’s motion response. As case study, the proposed programming code was applied to prediction motion responses of ship shape floating structure in surging, heaving, pitching, swaying, rolling and yawing directions. Results of simulation were compared with ANSYS AQWA software as bench mark. It found that the simulation results by the proposed programming code are similar with the ANSYS one.